2020
DOI: 10.1111/den.13686
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the safety and efficacy of peroral endoscopic myotomy between octogenarians and non‐octogenarians

Abstract: This study compared the safety and efficacy of peroral endoscopic myotomy for esophageal motility disorders between octogenarians and non-octogenarians. Methods: This retrospective observational study recruited 321 patients (28 octogenarians and 293 non-octogenarians) who underwent peroral endoscopic myotomy from two institutions. Clinical success (postoperative Eckardt score ≤ 3), technical success (completion of gastric and esophageal myotomy), and perioperative adverse events were compared between octogenar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 19 publications
(44 reference statements)
3
9
0
Order By: Relevance
“…Our octogenarian group had demographic characteristics similar to other authors that have studied and treated octogenarian patients with achalasia 29 30 31 , with some slight normal differences between populations, but without affecting the results of our study.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Our octogenarian group had demographic characteristics similar to other authors that have studied and treated octogenarian patients with achalasia 29 30 31 , with some slight normal differences between populations, but without affecting the results of our study.…”
Section: Discussionsupporting
confidence: 56%
“…POEM and LHM represent the cornerstone of treatment in young patients. POEM has a clinical success in octogenarians of > 90 %, but AE ranging from 5–7.8 %, most of them mild, but up to 10.7 % could be severe 7 29 30 31 . LHM has been associated with perioperative complications (bleeding [5–18 %], perforation [2 %–5 %], postsurgical infection [3 %–6 %]) 8 9 32 33 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…▶ 4 (2-6) arian patients with achalasia [29][30][31], with some slight normal differences between populations, but without affecting the results of our study. Biodegradable stent placement had a technical success of 100 %, with a mean placement duration of 37.5 ± 12.1 minutes, which is similar to reports using BS in other gastrointestinal diseases (42.1 ± 14 minutes) [18,19,22].…”
Section: Discussionmentioning
confidence: 41%
“…al demonstrated that POEM carries 93.4 % technical success and 90.8 % clinical success in 76 octogenarians with achalasia with 14.5 % AE rate, all mild to moderate in severity 4 . Octogenarians, compared to younger peers, experience higher incidence of perioperative AEs 4 18 . Thus, in an aging population, exploring supplementary treatment options seems logical- if not necessary 19 .…”
mentioning
confidence: 99%